2015
DOI: 10.1080/21645515.2015.1067350
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of adolescents with chronic medical conditions: Special considerations and strategies for enhancing uptake

Abstract: Adolescents with chronic medical conditions (CMCs), a growing population worldwide, possess a wide array of preventive health care needs. Vaccination is strongly recommended for the vast majority of these adolescents given their increased risk of vaccine preventable infection and associated complications. Not only should they receive routine vaccines, but some also require additional vaccines. Despite these guidelines, evidence suggests that adolescents with CMCs often fail to receive needed vaccines. Many fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 128 publications
(44 reference statements)
0
11
0
1
Order By: Relevance
“…Furthermore, studies have often linked delays in providing vaccinations, or non-vaccination, to doctors' lack of knowledge or failure to inform families of the indications for these particular vaccines. 7,8 Vaccination delay is defined as a notable difference between the actual and recommended age of vaccination, and it can be harmful. 9 The main objective of this study was to measure the vaccine coverage rates of children with chronic diseases in our university hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have often linked delays in providing vaccinations, or non-vaccination, to doctors' lack of knowledge or failure to inform families of the indications for these particular vaccines. 7,8 Vaccination delay is defined as a notable difference between the actual and recommended age of vaccination, and it can be harmful. 9 The main objective of this study was to measure the vaccine coverage rates of children with chronic diseases in our university hospital.…”
Section: Introductionmentioning
confidence: 99%
“…They do not receive systematic training for vaccinology and lack clinical experience, which prevents them from making the correct judgment for the precautions and contraindications of vaccination for CSHCN (21–24). In addition, due to the negative reports about vaccines and the lack of knowledge regarding the risk of vaccine preventable diseases, parents usually have many concerns for the use of vaccines (5). Finally, for clinical specialists, they have more concerns regarding AEFI if the child are suffering a chronic disease, such as seizures or suppressed immunologic system responses (25).…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore new strategies of improving the vaccination coverage of CSHCN, it was important to identify the main correlative factors that affect vaccination of this population. In the United States, demographic characteristics such as age, gender, insurance status are considered to be associated with vaccination coverage in youths with special health care (5, 26). In our study, we found that gender, family history of related diseases and history of mild or non-vaccine-related allergies were not strong factors influencing vaccination recommendations, which was consistent with the recommendation from “the guidelines for immunization of ACIP” and “Chinese Pharmacopeia”; nevertheless, we found that age, history of AEFI and the number of combined diseases were indicated as strong factors influencing vaccination recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…141516 These studies also underpin the importance of routine and annual immunizations for children with medical complexity to decrease infection-related risks. 1718 …”
mentioning
confidence: 99%